The prevalence of gestational diabetes among underweight and normal weight women worldwide: a scoping review - Gitlin, Emily S.; Demetres, Michelle; Vaidyanathan, Arthi; Palmer, Nicole; Lee, Hannah; Loureiro, Sabrina; Radwan, Eman; Tuschman, Abigail; Mathad, Jyoti; Chebrolu, Puja (Frontiers in Clinical Diabetes and Healthcare, 2024)
BackgroundGestational diabetes (GDM) affects nearly 15% of pregnancies worldwide and is increasing globally. While this growth is thought to be primarily from overweight and obesity, normal and underweight women are affected as well, particularly in low and middle-income countries. However, GDM in non-overweight women remains understudied. Thus, we examined the prevalence among normal and underweight women globally.MethodsA comprehensive literature search was performed in Ovid MEDLINE, Ovid EMBASE, and The Cochrane Library. Studies retrieved were screened for eligibility against predefined inclusion/exclusion criteria. Prevalence of GDM among women with normal and underweight body mass index (BMI) was extracted, and average prevalence was calculated globally, by World Health Organization region, and by country. Pregnancy outcomes were described when available.ResultsA total of 145 studies were included. The average global prevalence of GDM among non-overweight women (BMI <25 kg/m2) was 7.3% and among underweight women (BMI <18.5 kg/m2) was 5.0%. GDM prevalence in non-overweight women was highest in Asia (average 12.1%) and lowest in the African region (0.7%). The countries with the highest prevalence were Vietnam (21.1%), Finland (19.8%), Poland (19.3%), Bangladesh (18.65%), and China (17.7%). The average global prevalence of large for gestational age infants (LGA) born to non-overweight women with GDM was 9.9%, which is lower than the average prevalence in the general population with GDM (14%).ConclusionGDM is more common than previously recognized in non-overweight women, particularly in Asia, but also in European countries. Non-overweight women with GDM had lower prevalence of LGA babies compared to prior reported prevalence in all women with GDM, though data on pregnancy outcomes was limited. These findings challenge guidelines that recommend restriction of weight gain for GDM management. Further research on the pathophysiology and complications of GDM in women who are not overweight should be urgently conducted to inform appropriate management guidelines and support optimal pregnancy outcomes.